Improving Learning Achievement by Using Jigsaw Technique in Science Learning focusing on the topic of Preservation of Living Organisms on the Fifth Grade Semester I of SDN 2 Tribungan - Sunaryadi Sunaryadi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
Nowadays, a cooperative learning approach has been developed to produce well-learning objectives. At class that depends on teacher as the learning source, then lecture is the main option as the learning strategy. Therefore, a new strategy which is able to empower students is needed. A strategy that does not require the students to memorize facts, but rather a strategy that encourages them to construct knowledge by themselves. One of the learning achievements obtained is Science subject for grade V. Learning science emphasizes logical thinking ability, not memorizing facts. Based on the preliminary observation, the researcher conducted a classroom action research on Science subject on the fifth grade students of SDN 2 Tribungan at Managran district in the first semester by using Jigsaw technique. Based on the results of the research, it can be concluded that: 1) The improvement of students’ learning achievement showed that learning motivation was influenced by the learning strategy given by the teacher. High learning motivation influenced high learning achievement. 2) The prove of the improvement of students’ learning achievement could be explained in the results of cycle 4 activities. Based on the observation done in the previous cycles and cycle 4, there was found that 1) the students had understood and were ready to learn the material presented by the teacher, 2) Most of the students had been encouraged to express opinions during the class discussion, and 3) the activities ran well, the class atmosphere was more alive, so the learning process was fun.